Mobile shopping experience : The factors and emotions affecting the shopping experience on a smartphone - Pakarinen, Ville (My University, 2020)
With respect to their usage, online stores’ conversion rates on smartphones are still lower than on computers or desktops. Even though smartphones have their device limitations, there is still a monetary gap which could be diminished by knowing how to properly design an online shopping experience for a smartphone. This study adopts the idea behind Stimulus-Organism-Response model. Based on this model, an online store contains stimuli, which affect the customer’s organism. The organism can be divided to cognition and affect. The customer’s conscious behaviour is due to their cognition and unconscious behaviour due to affect, in other words emotions. Different emotions cause different behavioural responses and by knowing which emotions are the most significant in customers’ online shopping experience, customers’ actions can be predicted. This study’s purpose is to find out which stimuli, or factors, are most significant in m-shopping context and what emotions these factors evoke. To find out what these significant factors and emotions are, an experiment including three shopping tests was conducted. The shopping tests were carried out in ethical fashion apparel online stores. The experiment was done by ten participants. From these results was formed a list of 43 factors, which hold significance in customer’s online shopping experience. These 43 factors were divided in six main categories, which are named as content, navigation, visual, product, smartphone, and environment and internal state categories. The significant emotions inside each category were determined with the help of an emotion assessment tool called Geneva Emotion Wheel. Based on this study’s results, the navigation category is the most significant category for shopping experience, and the product category for shopping outcome. The shopping experience is not only affected by the online store’s design, but also by the online store’s products, environment, customer’s internal state and customer’s smartphone, though smartphone’s significance is small. The navigation and content factors evoke similar emotions and are relevant for completing a shopping task. The visual and product categories for their part evoke similar emotions and are important for attracting the customer. The taxonomy of significant factors and emotions provided in this study can be used by both researchers and managers alike to further study and plan an online shopping experience.

Vaikka älypuhelinten merkitys nyky-yhteiskunnassa on suuri, jää verkkokauppojen konversiot älypuhelimilla selatessa suhteessa tietokoneita pienemmiksi. Vaikka älypuhelimilla on omat rajoittavat tekijänsä, hyvän shoppailukokemuksen luomalla verkkokaupan konversiota älypuhelimella voitaisiin parantaa. Tämä tutkimus käyttää pohjanaan S-O-R mallia. Mallin mukaan verkkokauppa sisältää ärsykkeitä, mitkä vaikuttavat elimistöömme joko kognitiivisella- tai tunnetasolla. Asiakkaan tietoinen toiminta johtuu kognitiosta ja tiedostamaton toiminta puolestaan tunteista. Eri tunteet aiheuttavat erilaista käyttäytymistä, ja tietämällä mitkä tunteista ovat kaikkein merkittävimpiä asiakkaan shoppailukokemuksessa, yrityksen on mahdollista ennustaa asiakkaan käyttäytymistä. Tämän tutkimuksen tarkoitus on selvittää, mitkä ärsykkeet, toisin sanoen tekijät, ovat kaikkein merkittävimpiä mobiilikaupankäynnin kontekstissa ja mitä tunteita nämä tekijät herättävät. Tutkimusta varten luotiin koeasetelma, jossa toteutettiin shoppailutesti kolmessa eri eettisessä vaateverkkokaupassa. Koeasetelmaan osallistui kymmenen henkilöä. Tulosten perusteella muodostettiin 43 tekijän lista, jotka jaettiin kuuteen kategoriaan: sisältö-, navigointi-, visuaalisuus-, tuote-, älypuhelin- ja ympäristö ja sisäiset tekijät -kategorioihin. Merkittävät tunteet kategorioiden sisällä määritettiin tunnearviointityökalun, Geneva Emotion Wheel, avulla. Tulosten perusteella navigointitekijät ovat kaikkein merkittävimpiä shoppailukokemuksen kannalta ja tuotetekijät puolestaan shoppailun lopputuloksen kannalta. Shoppailukokemukseen ei vaikuta ainoastaan verkkokaupan design, vaan shoppailukokemuksen luonnissa on otettava huomioon ympäristö, jossa älypuhelinta selataan, kuluttajan sisäiset tekijät sekä kuluttajan älypuhelin, vaikkakin älypuhelimen merkitys tässä tutkimuksessa olikin pieni. Navigointi- ja sisältötekijät herättävät samanlaisia tunteita ja ovat tärkeitä shoppailun läpiviemisen kannalta. Visuaaliset- ja tuotetekijät puolestaan herättävät keskenään samanlaisia tunteita ja ovat tärkeitä kuluttajan kiinnostuksen herättämisessä. Tässä tutkimuksessa koottua listausta shoppailukokemukseen vaikuttavista tekijöistä ja tunteista voidaan käyttää tulevaisuudessa tutkijoiden ja yritysten toimesta tutkittaessa ja suunniteltaessa shoppailukokemusta.
Keywords: shopping experience, emotion, mobile commerce, ethical fashion apparel online store, Stimulus-Organism-Response model, Geneva Emotion Wheel